Islamic Financing Schemes and Return on Assets Empirical Evidence from BPRS Rahmah Hijrah Agung, Lhokseumawe - Yoesrizal Yoesoef; Ismail Ismail; Asra Febrian; Munawar Rizki Jailani; Imamuddin Imamuddin (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2026)
This study examines the influence of murabahah and musyarakah financing on profitability, measured through Return on Assets (ROA), at BPRS Rahmah Hijrah Agung in Lhokseumawe City over the 2014–2021 period. A quantitative research design was employed, drawing on quarterly financial statements published by the institution throughout the observation window. Using a saturated sampling technique, all 32 available quarterly reports were included as the study sample. Secondary data were retrieved from the official website of the Financial Services Authority (OJK) and subsequently analyzed through multiple linear regression using SPSS version 23. Before running the regression model, a series of classical assumption tests were conducted, namely the normality test (Kolmogorov-Smirnov), multicollinearity test (Variance Inflation Factor), autocorrelation test (Durbin-Watson), and heteroscedasticity test (Scatterplot). The findings reveal three key conclusions: (1) murabahah financing exerts a significant negative effect on ROA at the partial level, supported by a significance value of 0.015 < 0.05 and a t-statistic of −2.676, which exceeds the t-table value of 2.045 in absolute terms; (2) musyarakah financing does not produce a statistically significant effect on ROA at the partial level, as indicated by a significance value of 0.153 > 0.05 and a t-statistic of 1.491 < 2.045; and (3) when considered jointly, both murabahah and musyarakah financing exert a significant simultaneous effect on ROA, evidenced by a significance value of 0.006 < 0.05 and an F-statistic of 6.789, which surpasses the F-table value of 3.33. The coefficient of determination (R²) indicates that approximately 43% of the variation in ROA is accounted for by the two financing variables, while the remaining 57% is attributable to other factors beyond the scope of this study.